Revisión Sistemática de Estudios de Factores de Riesgo Psicosociales Asociados a la Pobreza y sus Efectos Neuropsicológicos en Población Infantil. - Navarro Yate, Linda Katerine; Orjuela Rivera, Jeidy Bibiana (Universidad Antonio Nariño, 2022)
The main objective of this research was to analyze the studies that addressed the investigation of psychosocial risk factors associated with poverty and its neuropsychological effects in the child population, through a systematic review in the last thirteen years, this research arises from the problem of poverty seen beyond economic scarcity, but as a predisposing factor in the proper development of children. The research was carried out under the mixed type, with descriptive methodological design and was used as an instrument to collect information sources such as studies published in the Scopus databases, Web Of Science, PubMed and the metasearch engine Google Scholar in the year 2003 to 2022, where it was agreed by the researchers different topics taken as reference categories: individual psychosocial risk factor, family, school and linked to peer group. From the search, 23 investigations were selected, in order to carry out a network analysis that would allow a detailed description of the investigations to be carried out and to identify the risk factors associated with poverty related to neuropsychological effects, a process by which answer to the problem question, since it was determined that exposure to the condition of poverty brings with it harmful effects on the development of children, among which processes of attention, memory and emotional self-regulation stand out.